CHARACTERIZATION OF GLYCOCUNJUGATE DISTRIBUTION IN THE EPIDIDYMIS OF THE JAVAN MUNTJACS (Muntiacus muntjak muntjak) - Sri Wahyuni; Hamny Sofyan; Hafizuddin Hafizuddin; I Ketut Mudite Adnyane; Gholib Gholib; Muhammad Jalaluddin; Fadli A. Gani; Mulyadi Adam; Tongku Nizwan Siregar; Srihadi Agungpriyono (Universitas Syiah Kuala, 2022)
The presence of glycoconjugates in caput, corpus, and cauda epididymis of the Javan muntjacs was performed using lectin histochemical method. The epididymis organs were obtained from two adult male Javan muntjacs in hard antler stage and then immediately fixed in Bouin’s solution and processed in histological manner. Six types of biotinylated lectins namely Peanut agglutinin (PNA), Soybean agglutinin (SBA), Wheat germ agglutinin (WGA), Ricinus communis agglutinin (RCA), Concanavalin A (Con A), and Ulex europaeus agglutinin I (UEA I) were applied to detect the specific glycoconjugates in the epididymal tissue of muntjacs. The result showed the presence of glycoconjugates were detected by five types of lectins except UEA I in caput, corpus, and cauda epididymis with specific distribution and also the intensity of lectins binding. Glycoconjugates β-galactose, β-glucose, mannose, N-acetyl-galactosamine, N-acetyl-glucosamine, and sialic acid were stained with various intensity in epithelial cells, basal cells, stereocilia, spermatozoa, and stroma of caput, corpus, and cauda epididymis. The presence of sialic acid on the surface of spermatozoa detected by WGA are thought to be play a role on sperm protection during their maturation and transit along epididymal lumen. In conclusion, the difference of glycoconjugates distribution pattern and lectin binding in the epididymal caput, corpus, and cauda of the Javan muntjac indicates the regional differences in epididymal function in spermatozoa maturation.